Augmented Reality Based Cultural Heritage in Improving Students' Literacy Culture in History Learning at SMK Muhammadiyah I Pekanbaru - Suroyo, Suroyo; Soedjiwo, Novena Ade Fredyarini; Entas, Derinta; Putra, Bima Maulana; Karimi, Amir; Soares, Antonio Constantino (Universitas Negeri Malang, 2025)
History learning in vocational high schools (SMK) is often faced with challenges in increasing students' interest and understanding of culture and history. The application of Cultural Heritage-based Augmented Reality (AR) technology as an innovative solution in improving students' literacy culture in history learning at SMK Muhammadiyah I Pekanbaru. This study aims to evaluate the impact of using Cultural Heritage-based AR on historical understanding, cultural appreciation, and student interest at SMK Muhammadiyah I Pekanbaru. Experimental research method was used with one experimental group engaged in learning using Cultural Heritage-based AR and one control group following conventional learning. Data were collected through knowledge test, questionnaire, and observation. The results showed that the use of Cultural Heritage-based AR significantly improved students' historical understanding, cultural appreciation, and interest in SMK Muhammadiyah I Pekanbaru. Students who use AR technology find the learning experience more engaging and interacting, which results in a deeper understanding of culture and history. This research makes a significant contribution in the context of history education at SMK Muhammadiyah I Pekanbaru, that Cultural Heritage-based AR can be an effective tool to improve students' literacy culture. In addition, the application of this technology can also help preserve and promote local cultural and historical heritage